Ibn al-Jazzar on fever - Abdul Razak, Fadhilah; Ismail, Ahmad Faris (IIUM Press, 2011)
The objective ofthis chapter is to discuss types of fever introduced by Ibn AI-Jazzar in his book entitled Zad al-Musafir wa-qut al-hadir which was translated by Gerrit Bos. According to Bos, since the book was written, none of the medical works of the Islamic physician dealing with fevers has been published in a critical edition and translation, thus make him decide to do so for our references. The significance of this chapter is to expose the contribution by Ibn AI-Jazzar as one of our Muslim scholars on fever during his time. The method used in this chapter is by referring to the translation of original text by Ibn AIJazzar, journals as well as reliable online references. The research framework covers type of fevers during time ofIbn AI-Jazzar, the symptoms and treatment suggested by him and the enhancement done in medical field in identifying specific kind of fevers by referring to the findings from the scholar